Knowledge and response of health care workers after needle - stick injury in a tertiary care hospital setting in tribal Rajnandgaon, Chhattisgarh, India - Makade, Kiran G.; Bhawnani, Dhiraj; Verma, Nirmal; Dengani, Monika (International Journal of Research in Medical Sciences, 2017)
Background: Health care workers (HCW) who have occupational exposure to blood are at increased risk for acquiring blood-borne infections. Occupational exposure to blood can result from per-cutaneous injury (needle stick or other sharps injury), muco-cutaneous injury or contact with non-intact skin. Hence not only doctors and nurses even laboratory technicians, housekeeping personnel and hospital waste handlers are at risk of harboring the blood borne infections through needle-stick injury (NSI). Methods: The present prospective cross sectional study was carried out at the 400 bedded Government Medical College Hospital, Rajnandgaon, Chhattisgarh, India, during period from November 2015 to August 2016. Out of total study participants, 18 were doctors, 142 nurses and 20 lab technicians from different clinical departments/wards of the hospital. Data was collected by using a predesigned pretested questionnaire and analyzed using appropriate statistical software. Results: Out of 180 HCW, 149 (82.78%) were females and, 31 (17.22%) were males. Majority 78 (43.3%) of the subjects said that the physician should be consulted after NSI within one hour. 51.1% of the subjects surprisingly replied that it was not necessary to report NSI. Around 72 (40%) of the subjects had history of NSI sometime in their life till then. Out of total exposed respondents, 56/72 (77.8%), took ICTC consultation. Out of total subjects who consulted ICTC, 51/56 (91.1 %), were suggested to take PEP by the ICTC physician. Out of 51 subjects who were advised PEP (Post Exposure Prophylaxis) by ICTC Physician, 45 (88.2%) started PEP within 1 hr of NSI. Majority of the participants replied that most probability of getting NSI was while drawing blood sample from the patients (29.2%). 68.9% of the study subjects were immunized completely against Hepatitis B. Conclusions: The study subjects had adequate knowledge about NSI and their response in the form of actions that have to be taken after NSI was also satisfactory. The response in the form of taking consultation from a specialist and taking PEP was appreciable but it needs to be improved upon.